KONSEP BELAJAR DALAM AL-QUR’AN (TELAAH TAFSIR AL-MISBAH SURAT AL-‘ALAQ AYAT 1-5) - Afifatu Nur Arifah; Rosichin Mansur; Dzulfikar Rodafi (VICRATINA, 2020)
This Study aims to examine about learning contained in the Al-Qur’an surah Al-‘Alaq ayat 1-5, because this ayat contains the meaning that explain about concepts in learning and teaching activities are available. Learning is an activitiy that will bring a big influence on the facer then with this will be even more perfect in the context of the chain refersto the Al-Qur’an which one Al-Qur’an is main source in life for more perfect understanding of writing of Al-Qur’an then in this study the writer is quided by “Tafsir Al-Misbah Pesan dan Keserasian al-Qur’an” creation M. Quraish Shihab. The result of the study are explained about the monotheims material contained in the surah al-‘Alaq ayat 1-5. Explained anyway about the repetition method which can be applied in theaching and learning activities trough the reading command mentioned in ayat first and thrid. And the inquiry strategy described in Al-Qur’an surah Al-‘Alaq ayat 1-5 through the reading command contained there in. Kata Kunci: Konsep Belajar, Al-‘Alaq ayat 1-5Kata Kunci: Konsep Belajar, Al-‘Alaq ayat 1-5